Comparison of the Different Type and the Different Routes of Administration of Human Chorionic Gonadotropin During Trigger of Ovulation in ICSI Cycles and the Relation with Body Mass Index - Moraloğlu, Özlem; Kılıç, Sevtap; Özakşit, Gülnur; Yüksel, Beril; Işık, Ayça; Mollamahmutoğlu, Leyla (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: To confirm that HcG levels in follicular fluid and serum after intramuscular (IM) or subcutaneous(SC) administration of purified (p)HcG and SC administration of recombinant(r)HcG and their associations with body mass index (BMI) and oocytes maturation in ICSI cyle. STUDY DESIGN: We used pHcG or rHcG for triggering ovulation of all patients . Group1(n:56) received IMpHcG and Group2(n:57) received SCpHcG and Group3( n:47) received rHcG . Serum and follicular fluid HcG levels were measured on the day of oocytes retrieved as primary outcome. RESULT: There was a significant difference on serum and follicular fluid HcG levels among three groups. No correlation was found between BMI and oocytes maturation for Group1 and Group2. But there was a significantly negative correlation between BMI and oocytes maturation in Group3. CONCLUSION: When comparing the different administration routes of HcG , the S.C. route of HcG seems to be safer and useful for obese patients.